2020
DOI: 10.2459/jcm.0000000000001145
|View full text |Cite
|
Sign up to set email alerts
|

Threshold for calcium volume evaluation in patients with aortic valve stenosis: correlation with Agatston score

Abstract: Background The evaluation of aortic valve calcium burden is important when planning for transcatheter aortic valve implantation (TAVI). Although a robust golden standard methodology is available for calcium evaluation on noncontrast-enhanced (NCE) computed tomographic (CT) series, a standard reference for calcium assessment on contrast-enhanced CT series is currently lacking. Methods Two hundred and forty-four preprocedural CT scans from patients who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Transcatheter aortic valve replacement (TAVR) is the treatment of choice for patients with severe symptomatic aortic stenosis and has become the preferred strategy in patients at intermediate/high surgical risk 1–5 . In the last decade, many efforts have been made to improve patient selection for TAVR, and reduce procedural complications and adverse outcomes 6–13 . In patients undergoing TAVR, prosthesis adaptation to the aortic root is of paramount importance to avoid severe paravalvular leaks, achieve an effective orifice area and minimize patient–prosthesis mismatch 14,15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcatheter aortic valve replacement (TAVR) is the treatment of choice for patients with severe symptomatic aortic stenosis and has become the preferred strategy in patients at intermediate/high surgical risk 1–5 . In the last decade, many efforts have been made to improve patient selection for TAVR, and reduce procedural complications and adverse outcomes 6–13 . In patients undergoing TAVR, prosthesis adaptation to the aortic root is of paramount importance to avoid severe paravalvular leaks, achieve an effective orifice area and minimize patient–prosthesis mismatch 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In the last decade, many efforts have been made to improve patient selection for TAVR, and reduce procedural complications and adverse outcomes. [6][7][8][9][10][11][12][13] In patients undergoing TAVR, prosthesis adaptation to the aortic root is of paramount importance to avoid severe paravalvular leaks, achieve an effective orifice area and minimize patientprosthesis mismatch. 14,15 Of interest, it is widely described that TAVR with a balloon-expandable valve was systematically associated with a certain degree of valve stent recoil.…”
Section: Introductionmentioning
confidence: 99%
“…25 The calcium score assessment by using the Agatston score before TAVI is essential; in patients with LV outflow tract (LVOT) Hounsfield unit (HU) of less than 300, the correct threshold to be set in the CT software is 450 HU, whereas in patients with LVOT HU of at least 300 the correct threshold is 850 HU. 26 It has also been shown that psoas muscular attenuation CT measurement (mean HU and high-density/low-density muscle) are independent and incremental predictors of allcause mortality in patients undergoing TAVI. 27 CT is also crucial for the success of transcatheter valve replacement, allowing a complete evaluation of mitral and tricuspid apparatus and biventricular anatomy.…”
mentioning
confidence: 98%
“…The calcium score assessment by using the Agatston score before TAVI is essential; in patients with LV outflow tract (LVOT) Hounsfield unit (HU) of less than 300, the correct threshold to be set in the CT software is 450 HU, whereas in patients with LVOT HU of at least 300 the correct threshold is 850 HU 26 …”
mentioning
confidence: 99%
“…Abbreviations: AR, aortic regurgitation; AV, aortic valve; CT, computerized tomography; LVEF, left ventricular ejection fraction; Pt, patient; RCC, right coronary cusp; STS, Society of Thoracic Surgeons; THV, transcatheter heart valve; VBR, virtual basal ring. a Measured at 850 HU using automated 3mensio Structural Heart 10.2 software 9. …”
mentioning
confidence: 99%